Cancer Stem Cells and Immunosuppressive Microenvironment in Glioma - Ma, Qianquan; Long, Wenyong; Xing, Changsheng; Chu, Junjun; Luo, Mei; Wang, Helen Y.; Liu, Qing; Wang, Rong-Fu (Frontiers in Immunology, 2018)
Glioma is one of the most common malignant tumor of the central nervous system and is characterized by extensive infiltrative growth, neovascularization, and resistance to various combined therapies. In addition to heterogenous population of tumor cells, the glioma stem cells (GSCs) and other nontumor cells present in the glioma microenvironment serve as critical regulators of tumor progression and recurrence. In this review, we discuss the role of several resident or peripheral factors with distinct tumor-promoting features and their dynamic interactions in the development of glioma. Localized antitumor factors could be silenced or even converted to suppressive phenotypes, due to stemness-related cell reprograming and immunosuppressive mediators in glioma-derived microenvironment. Therefore, we also summarize the latest knowledge on GSCs and key microenvironment components, and discuss the emerging immunotherapeutic strategies to cure this disease.